The Effect of the COVID-19 Pandemic on Mental Health among College Students in the United States - Sahay, Smita; Flora-Annabelle Vargas, Christina; Claire Hoar, Sophia; Choi, Jae; Marie O'Donovan, Sinead (Translation: The University of Toledo Journal of Medical Sciences, 2024)
The COVID-19 pandemic has significantly impacted the mental health of college students in the United States (U.S.). Here, we review studies that explored the effect of the COVID-19 pandemic on mental health measures and coping strategies of university students. Previously published studies conducted in this population, using tools like the PHQ-9, GAD-7, and PSS-10 questionnaires demonstrated a notable increase in the prevalence of depression, anxiety, stress and suicidal ideation. Female and advanced college students were particularly vulnerable, consistently showing higher scores for anxiety and stress. Females also displayed greater depression severity scores compared to their male counterparts; however, some advanced students displayed lower scores compared to the first-year undergraduate students. There was an overall decrease in suicidal ideation among college students during the pandemic; however, some schools were found to have an increase in the level of suicidal ideation. The shared negative effects of COVID-19 among college students encompassed health, academic, and lifestyle domains. Coping strategies varied, with "support from friends and family" being predominant. In addition, an overall underutilization of mental health resources was reported. Non-pharmacological therapies, particularly lifestyle modifications such as regular exercise, demonstrated efficacy in alleviating symptoms; however, challenges such as underuse and patient compliance were prevalent. These findings highlight the necessity of promoting mental health resources, addressing gender and academic level-specific vulnerabilities, and implementing accessible non-pharmacological interventions to mitigate the mental health impact of pandemics on U.S. college students.